Effects of thawing method on palatability and thawing characteristics of beef loins - Decker, Lindsey (Kansas State University, 2023)
The objective of this study was to investigate the effects of various thawing methods on beef palatability. USDA Choice paired beef strip loins (n = 15) were obtained from a Midwest commercial processing facility for palatability evaluation. Moreover, 6 USDA Low Choice strip loins for thawing characteristic data collection were collected. At day 11 of aging, the paired strip loins were portioned into 6 blocks, and fabricated into 2.5 cm steaks. Each block was then assigned one of six thawing methods, with each loin containing each thawing method. Thaw methods included the four USDA approved thawing methods: thawing in the refrigerator(2-3° C; 882 m), cold water (2-3° C; 637.5 m), microwave (50% power, 7 m), and cooking from frozen, as well as two methods commonly used by consumers: thawing in hot water (40° C; 10.3 m), and on the counter (19±1° C; 264 m). Within each block, steaks were assigned to one of four tests: consumer panel, trained panel, Warner-Bratzler shear force, and lab assay. Steaks were aged a total of 21d prior to freezing. Loins designated for thawing characteristic data collection were fabricated into 2.5 cm steaks at 11 d of aging, assigned a random thawing treatment. Temperature probes were inserted, vacuum packaged, and frozen. End-point thawing temperature was targeted at 0°C for all steaks. For thawing characteristic steaks, temperature probes were connected to data loggers immediately upon removal from the freezer, Thaw rate, time, and temperature at times prior to thawing were all recorded from –6.67° C to 0° C. Data were analyzed as a completely randomized block design. Results from consumer panels indicate no differences (P > 0.05) among all thawing methods for consumer’s ratings for tenderness, juiciness, flavor, and overall liking. Similarly, there were no differences (P > 0.05) among thawing methods for percentage of steaks rated acceptable for tenderness, juiciness, flavor, and overall liking. Moreover, there were no differences (P > 0.05) in consumer perception of quality. In terms of myofibrillar tenderness in trained sensory panels, thawing in the refrigerator and cold water were more tender (P < 0.05) than cooking from frozen, while thawing in the refrigerator and cold water were rated higher for overall tenderness by trained sensory panelists than thawing in the microwave and cooking from frozen. Moreover, cooking steaks from frozen was rated higher (P < 0.05) for beef flavor intensity for all thawing methods. Lastly, there were no differences (P > 0.05) for initial juiciness, sustained juiciness, connective tissue, Warner- Bratzler Shear Force, and slice shear force. In terms of objective quality measurements, thawing steaks in the microwave had lower (P < 0.05) a* and b* values than all other thawing methods, while cooking from frozen steaks had lower a* and b* values than thawing on the counter. Additionally, steaks thawing in the microwave had the highest (P < 0.05) cook loss, followed by cooking from frozen, with all other methods being similar. Similarly, steaks thawed in the microwave and in hot water had a higher (P < 0.05) thawing loss than thawing on the counter, in cold water, and in the refrigerator. Also, steaks thawed in the microwave had the highest (P < 0.05) total moisture loss, followed by hot water and cooking from frozen, then thawing in cold water, on the countertop, and in the refrigerator. Lastly, steaks cooked from frozen had a higher (P < 0.05) expressible moisture than thawing steaks on the counter, in colder water, or in the refrigerator. These results indicate thawing method had minimal differences on overall palatability, and objective quality measures. Although, increases in thawing loss should be considered when thawing large quantities of meat for potential overall economic loss. Therefore, consumers and food service establishments should use their preferred thaw method, taking food safety and time into consideration.
Keywords: Beef; Sensory; Thawing; Trained panel; Consumer panel